Community Health Workers: An Underappreciated Asset to Tackle NCD - Jarvis, Jordan D.; Kataria, Ishu; Murgor, Mellany; Mbau, Lilian (Elsevier Ltd., 2016)
With continued undernutrition and escalating overnutrition, urbanization, and resource-strapped health systems, nations—particularly those in the low- and middle-income brackets—are facing the harsh reality of a growing double burden of communicable and noncommunicable diseases (NCD) [1,2]. The dearth of a skilled health workforce is a principal concern when it comes to tackling these challenges, as health care systems and health care training programs are set up to respond to acute care needs and struggle to deliver prevention and care for chronic conditions [3,4]. Although efforts to ramp up education and training on NCD among physicians, pharmacists, nurses, and other skilled health workers is urgently needed and must be prioritized, empowered Community Health Workers (CHW) present a secret weapon to combating NCD.
From the *Young Professionals Chronic Disease Network, Global, Boston, MA, USA; yUniversity of Delhi, New Delhi, India; and zAmref Health Africa in Kenya, Nairobi, Kenya.
Keywords: New Delhi; Undernutrition; Community Health workers (CHWs); NCD; Non-communicable diseases (NCD); Kenya; India; Bangladesh; Nigeria